2021
DOI: 10.1002/ejp.1725
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in cognitive–affective processes in adults with chronic pain

Abstract: Background: Chronic pain is associated with significant physical and psychological impairments across the adult lifespan. However, there is a relative gap in knowledge on individual differences that predict pain-related functioning. The current study highlights one important source of individual variation: age. Methods: We used cross-sectional data from a large treatment-seeking cohort of 2,905 adults (M age = 46.6 [13.1]; 71.8% women) presenting to a tertiary pain centre in the United Kingdom to determine age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…This evidence allows suggesting that elders might have poorer outcomes concerning the emotional processing of pain, regardless of the reduction in pain sensitivity. In contrast, a clinical study revealed that older adults aging from 65 to 75 years, presenting with chronic pain diagnosis, had a superior pain acceptance and self-efficacy, with less catastrophizing levels, in comparison with middle-aged and young adults ( Murray et al, 2021 ). Thus, older individuals apparently perform better with pain experiences, with inferior levels of pain-related depression and disability when contrasted with younger individuals.…”
Section: Pain Transmission and Experience In The Geriatric Populationmentioning
confidence: 96%
“…This evidence allows suggesting that elders might have poorer outcomes concerning the emotional processing of pain, regardless of the reduction in pain sensitivity. In contrast, a clinical study revealed that older adults aging from 65 to 75 years, presenting with chronic pain diagnosis, had a superior pain acceptance and self-efficacy, with less catastrophizing levels, in comparison with middle-aged and young adults ( Murray et al, 2021 ). Thus, older individuals apparently perform better with pain experiences, with inferior levels of pain-related depression and disability when contrasted with younger individuals.…”
Section: Pain Transmission and Experience In The Geriatric Populationmentioning
confidence: 96%
“…Publication bias was assessed through Egger’s test and funnel plots using at least ten studies [ 34 ]. Subgroup analyses were conducted to examine the potential sources of heterogeneity, including age (young (18–39 years old)/middle-age (40–64 years old)/both) [ 35 ], BMI (BMI < 25/BMI ≥ 25), menopausal status (postmenopausal/premenopausal/both), country, and ethnicity. All statistical analyses were performed with Review Manager, version 5.4.1 (The Cochrane Collaboration, London, UK, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In pain research, emerging adults are often grouped with cohorts of adolescents and adults. This is a disservice as emerging adulthood is a distinct developmental stage and thus the needs of emerging adults living with chronic pain are unique 16 . For example, emerging adults with chronic pain are often transitioning from pediatric to adult care for their pain treatment, which may also coincide with the transition to living independently to join the workforce, enlist in the military, and/or attend university 17,18 …”
Section: Aim Of the Reviewmentioning
confidence: 99%
“…This is a disservice as emerging adulthood is a distinct developmental stage and thus the needs of emerging adults living with chronic pain are unique. 16 For example, emerging adults with chronic pain are often transitioning from pediatric to adult care for their pain treatment, which may also coincide with the transition to living independently to join the workforce, enlist in the military, and/or attend university. 17,18 The aim of this narrative review is to propose a framework for understanding the role of parents (eg, parental distress and helicopter parenting) in the chronic pain experience of an emerging adult.…”
mentioning
confidence: 99%